Síntese de NiFe2O4 a partir do níquel reciclado de baterias Ni-MH e suas aplicações multifuncionais como um catalisador em processos foto Fenton e como um pseudocapacitor eletroquímico - Magnago, Luma Barbosa (2018)
In this study, a co-precipitation method was used for the synthesis of undoped ferrites (Fe2O3/Fe3O4-R) and nickel-doped ferrites from nickel reagents (NiFe2O4-R) and from nickel recycled from spent nickel–metal hydride (Ni-MH) batteries (NiFe2O4-B). Ferrite structure and composition were confirmed by X-ray diffraction (XRD), energy dispersive X-ray (EDX) and inductively coupled plasma optical emission spectrometry(ICP-OES). Scanning electron microscopy (SEM) showed agglomerated particles of different sizes and shapes and the transmission electron microscopy (TEM) revealed spherical particles of 50 nm. Ferrites are a multifunctional material that can be used as a catalyst and pseudocapacitor. The catalytic properties of ferrites were analyzed by measuring the decolorization of methylene blue (MB) in a photo-Fenton process under solar radiation. The experimental design ranked ferrites in the following order of MB decolorization efficiency: NiFe2O4-B = NiFe2O4-R > Fe2O3/Fe3O4-R. Using NiFe2O4-B, MB solutions were decolorizedwith more than 90% efficiency in 90 min. ICP-OES analyzes of the solution contained indetected concentrations of (0.00057 ± 0.00067) mg L-1of nickel ions and undetected concentration of ironions. The concentrations of nickel and iron ions arelower than the standard effluent release concentrations indicated CONAMA resolution 430/2011. NiFe2O4-B ferritedoes not transfer metals ions present in its composition to the solution. Analysis of the MB solution by ion chromatography after the NiFe2O4-B-catalyzed decolorization showed the presence of formic, acetic, and propionic acids.Pseudocapacitive properties, analyzed by cyclic voltammetry, showed that NiFe2O4-B have higher charge efficiency (84.3%) when compared with NiFe2O4-R (65.5%) and Fe2O3/Fe3O4-R (57%) after 1000 cycles. Ferrite NiFe2O4-B is an efficient catalyst for MB degradation andas pseudocapacitor